Inter- and intra-examiner agreement of three classification systems of gingival recession - Fatemeh Sarlati; Omid Moghaddas; Reza Shabahangfar; Sara Safari; Naser Valaei (Tabriz University of Medical Sciences, 2019)
Background. Several classifications have been proposed for gingival recession defects. Correct diagnosis of the type of gingival recession is necessary for proper treatment planning and assessment of the prognosis. Considering the existing uncertainty regarding the reliability of different classification systems available for gingival recession and their shortcomings, this study sought to assess the reproducibility and reliability of accuracy of three available classifications (Cairo, Mahajan and Miller's classification systems) for gingival recession. Methods. This descriptive study was conducted on 32 patients presenting to the Department of Periodontics, who were selected using convenience sampling. The screening process entailed two sessions and those with a minimum of one site of gingival recession disclosing the cementoenamel junction (CEJ) of the tooth with no adjacent tooth loss at the site of recession were enrolled. Each patient was separately evaluated by three calibrated examiners twice with a minimum of one-week interval. Grading of the gingival recession defects was determined using the Cairo, Mahajan and Miller's classification systems for gingival recession. The gradings of each examiner were separately recorded by a blinded examiner. A total of 120 single recession defects were examined and data were analyzed using intra-class correlation coefficient (ICC) and Spearman's test. Level of agreement was evaluated according to Landis and Koch. Results. The results showed that the reliability of all the three methods was almost perfect (P<0.05), and no significant difference was noted in reliability of the Cairo, Mahajan and Miller's classifications for gingival recession (P=0.7). Conclusion. Based on the results of the study, the highest intra- and inter-observer agreement in the use of the three classifications belonged to the Cairo classification; however, all the three classifications showed high reliability